CONTRIBUTIONS MARINE TOURISM OPPORTUNITY TO WORK AND FISHERMAN HOUSEHOLD INCOME LEVEL ON THE ROMANTIC BEACH SEI NAGALAWAN VILLAGE PERBAUNGANSUBDISTRICT OF SERDANG BEDAGAI REGENCY NORTH SUMATERA PROVINCE - Dony Murryananda G; Kusai Kusai; Darwis Darwis (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research was conducted in January 2018 in Sei Nagalawan Village, Perbaungan Serdang Bedagai Regency of North Sumatra Province. The purpose of this study to determine the amount of employment opportunities and how much contribution of marine tourism-related business to the level of income household fishermen. The method used in this research is survey method. Retrieval of respondents using the technique proportional sampling of 19% of the total population. Analysis of the data used is qualitative and quantitative analysis.These results show indicate the magnitude of employment opportunities, especially in the informal businesses in the tourism sector can be seen from the 2017 Households increase in business is growing coastal fishing before totaling 17 business units with as many as 24 workers. Then after the beach is growing up to 42 units of businesses with employees 54 people. On average the fisheries industry accounted for 53.69% of total family income for one month. While the tourism industry and other businesses contributed an average of 36.66% and 9.65% of total household income for one month. Keywords: Employment , Contribution, Household, Fisherman